How do Different Nutritional Approaches Impact Quality of Life and Disease Symptoms in Parkinson's Disease Patients over A 12-Month Period? : A Systematic Review - Muhammad Jabbar Rahman Tapiheru; Maysaroh Ritonga; Yoga Reza Fauzi (International Medical Journal Corp. Ltd, 2025)
Introduction: Parkinson's disease (PD) is a progressive neurodegenerative disorder where motor and non-motor symptoms significantly impact quality of life. While pharmacological treatments are standard, they have limitations, prompting interest in complementary strategies like nutrition. This systematic review evaluates the impact of various nutritional approaches on quality of life and disease symptoms in PD patients. Methods: Adhering to PRISMA guidelines, we systematically reviewed literature from PubMed, Semantic Scholar, Springer, and Google Scholar. The review included randomized controlled trials, systematic reviews, and meta-analyses evaluating nutritional interventions in adults with PD over a 12-month period, focusing on quality of life and disease symptom outcomes. A narrative synthesis was conducted due to the heterogeneity of the studies. Results: Sixteen studies were included, comprising ten trials and six systematic reviews. Promising interventions that significantly improved motor symptoms included the Mediterranean diet, protein redistribution diet, and supplements like probiotics, niacin, hydrogen water, and fermented papaya. Probiotics and niacin also demonstrated significant benefits for non-motor symptoms and quality of life. Discussion: The findings suggest that certain nutritional strategies, particularly the Mediterranean diet and supplementation with probiotics and niacin, hold significant potential as adjunct therapies in PD management. Conclusion: Nutritional interventions show considerable promise for improving both motor and non-motor symptoms in Parkinson's disease. Probiotics, the Mediterranean diet, and niacin appear particularly beneficial.